Notch functions in developmental and tumour angiogenesis by diverse mechanisms1. (17th November 2014) - Kangsamaksin, Thaned; Tattersall, Ian W.; Kitajewski, Jan
Abstract : The Notch signalling pathway is a key regulator of developmental and tumour angiogenesis. Inhibition of Delta-like 4 (Dll4)-mediated Notch signalling results in hyper-sprouting, demonstrating that Notch regulates tip-stalk cell identity in developing tissues and tumours. Paradoxically, Dll4 blockade leads to reduced tumour growth because the newly growing vessels are poorly perfused. To explore the potential for targeting Notch, we developed Notch inhibitors, termed the Notch1 decoys. A Notch1 decoy variant containing all 36 epidermal growth factor (EGF)-like repeats of the extracellular domain of rat Notch1 has been shown to inhibit both Dll and Jagged class Notch ligands. Thus this Notch1 decoy functions differently than Dll4-specific blockade, although it has the potential to inhibit Dll4 activity. Expression of the Notch1 decoy in mice disrupted tumour angiogenesis and inhibited tumour growth. To understand the mechanism by which Notch blockade acts, it is important to note that Notch can function in multiple cell types that make up the vasculature, including endothelial cells and perivascular cells. We investigated Notch function in retinal microglia and determined how myeloid-expressed Notch can influence macrophages and angiogenesis. We found that myeloid-specific loss of Notch1 reduced microglia recruitment and led to improper microglia localization during retinal angiogenesis. Thus either pharmacological inhibition of Notch signalling or genetic deficiencies of Notch function in microglia leads to abnormal angiogenesis.